Pay, risk, and productivity: The case of Finland, 1980 - 1996 - Eva M. Meyersson-Milgrom; Trond Petersen; Rita Asplund (The Research Institute of the Finnish Economy (ETLA), 2000)
In this paper we report on four topics. (1) To what extent are piece-rate systems used among manufacturing workers in Finland? (2) What is the effect on the average pay level of using piece- versus time-rate systems? (3) How much wage risk is associated with a piecerate system? (4) How much of the pay differential between piece- and time-rate workers is compensation for extra effort and how much is compensation for bearing additional risk? How do the studied years 1980, 1990, and 1996 differ with respect to the four questions? We have access to unique individual-level data on payment system (piece- versus time-rate) and occupation from several thousand establishments and more than a quarter of a million individuals engaged in the private sector in Finland. The central findings are that a majority of the studied employees work on time rate only and that there has been a shift from mixed piece-rate schemes to only piece-rate schemes between 1980, 1990 and 1996. Second, there is a substantial extra payoff from working at a piece-rate scheme. Third, piece-rate jobs entail a risk of loss: A nonnegligible percentage of the piece-rate workers earn less than the time-rate workers at the same occupation–establishment level. Fourth, there is evidence of risk compensation: The higher the variance of pay at the occupation–establishment level, the higher the average pay at that level is. Finally, most of the pay differential between time- and piece-rate workers is compensation for extra effort and a smaller part consists of compensation for risk, which confirms that there are strong productivity gains from the use of piece rate. – – Käsittelemme tässä raportissa neljää eri teemaa: (1) Missä määrin suorituspalkkausta käytetään Suomen tehdasteollisuudessa? (2) Miten suorituspalkkauksen käyttäminen vaikuttaa keskipalkkatasoon aikapalkkaukseen verrattuna? (3) Miten suuri palkkariski liittyy suorituspalkkaukseen? (4) Kuinka suuri osa suoritus- ja aikapalkkaustyöntekijöiden välisestä palkkaerosta on korvausta ylimääräisistä ponnisteluista, ja kuinka suuri osuus taas on korvausta ylimääräisestä riskinotosta? Miten tarkasteltavien vuosien, 1980, 1990 ja 1996, tilanne eroaa näiden neljän kysymyksen osalta? Meillä on pääsy ainutlaatuiseen palkkaustapaa (suoritus-tai aikapalkka) ja työtehtävää koskevaan yksilötason tilastoaineistoon. Kyseinen aineisto sisältää tiedot useista tuhansista yksityisen sektorin toimipaikoista Suomessa ja kattaa yli neljännesmiljoona työntekijää. Saadut tulokset osoittavat, että suurin osa tutkituista työntekijöistä työskentelee pelkästään aikapalkalla, ja että vuosien 1980 ja 1996 välillä on tapahtunut siirtymä yhdistetyistä suorituspalkkajärjestelmistä (suoritus- ja aikapalkkojen yhdistelmistä) puhtaisiin suorituspalkkoihin. Lisäksi suorituspalkan havaitaan tuottavan työntekijälle huomattavan ansiolisän. Edelleen havaitaan suorituspalkkaukseen liittyvän myös riski menettää rahaa: tietty, ei aivan vähäpätöinen, prosentti-osuus suorituspalkkalaisista ansaitsee vähemmän kuin vastaavalla työtehtävä-yritys -tasolla olevat aikapalkatut työntekijät. Tätä riskiä kompensoi kuitenkin havainto, että palkat ovat tietyllä työtehtävä-yritys -tasolla sitä korkeammat, mitä suurempi palkkojen vaihtelu on sillä tasolla. Lopuksi huomataan, että suurin osa suorituspalkkaus- ja aikapalkkaustyöntekijöiden välisestä ansioerosta pohjautuu kompensaatioon ylimääräisestä ponnistelusta, ja vain pieni osa perustuu korvaukseen riskinotosta. Siten suorituspalkkauksen käyttö selvästi kasvattaa tuottavuutta. – palkkajärjestelmä ; tuottavuus ; riski ; suorituspalkka ; aikapalkka
Keywords: 330; pay system; productivity; risk; piece-rate pay; time-rate pay; Vergütungssystem; Zeitlohn; Leistungsorientierte Vergütung; Finnland